Indonesia’s Rational Choice in Facing Myanmar’s Conflict During Its 2023 ASEAN’s Chairmanship - Fachrie, Muhammad (Global and Policy Journal of International Relations, 2025)
This research explains what the rational choice is for Indonesia in facing Myanmar’s conflict in the context of Indonesia 2023 ASEAN’s chairmanship. This conflict involves various actors, which consist of ethnic groups, political actors, states, international organizations, and great powers. It is rooted in historical, political, and socio-economic grievances, with deep-seated ethnic and religious divisions exacerbating tensions. The military coup in February 2021 has further escalated the conflict, leading to widespread protests, violence, and human rights abuses, which attract regional and international concern. The international community, including ASEAN, its members, the UN, and great powers, have attempted to communicate, mediate, and facilitate a resolution to the crisis and even took an interest in this conflict. This research uses the qualitative method by collecting and analyzing secondary data published by institutions, organizations, and other sources. Then, rational choice and Stag Hunt are used to analyze the collected data in order to answer the problem of this research. Eventually, this research finds that the rational choice of Indonesia in facing Myanmar’s conflict on its chairmanship is the behavior of other actors (ASEAN, its members, US, China, and Russia) because there is no assurance that other actors would support cooperation in resolving Myanmar’s conflict.